Effect of N‐Alkyl Substituents on the Hierarchical Self‐Assembly of β‐Cyclodextrin‐Linked Pyrene‐Pyromellitic Diimide Charge‐Transfer Complexes. Issue 44 (10th July 2018) - Krishnan, Sumesh Babu; Krishnan, Retheesh; Gopidas, Karical Raman
Abstract: Hierarchical self‐assemblies of β‐cyclodextrin‐linked pyrene and N ‐alkyl derivatives of pyromellitic diimides are studied in detail. The charge‐transfer interaction between pyrene and pyromellitic diimide is augmented by β‐cyclodextrin–pyromellitic diimide binding interactions in these cases. When the alkyl group is adamantyl, a 1:1 complex was formed with a very high association constant ( K a =1.82×10 6 m −1 ). Here, the charge‐transfer interaction is reinforced by inclusion binding of the adamantyl group in the β‐cyclodextrin cavity leading to the formation of 2D sheets, which undergo twisting to give twisted fibres. When the alkyl group is tert ‐butyl, a 1:2 complex was formed with a high association constant ( K a =2.91×10 4 m −1 ). A detailed analysis showed that the tert ‐butyl pyromellitic diimide undergoes both inclusion and rim‐binding interactions with the β‐cyclodextrin. The charge‐transfer complex further self‐assembled into chiral nanostructures as evident from SEM, TEM and AFM analysis. In the case of N ‐methyl‐substituted pyromellitic diimide, the interaction with β‐cyclodextrin‐linked pyrene was only through rim binding, which resulted in the formation of a weak charge‐transfer complex with K a =4.2×10 3 m −1 . Formation of a hierarchical assembly was not observed in this case. A rational mechanism for the self‐assembly, which relies on the strength of the cyclodextrin–pyromellitic diimide complexation is presented. Abstract : Complex construction kit : The self‐assembly in β‐cyclodextrin‐appended pyrene– N ‐substituted pyromellitic diimide charge‐transfer systems is governed by the structure of the nitrogen substituent (see figure).